The Drunken Officials of Abdülhamid II: Alcohol Consumption in the Late Ottoman Bureaucracy - Abdulhamit Kırmızı (Revue des Mondes Musulmans et de la Méditerranée, 2022)
Sultan Abdülhamid II (r. 1876-1909) has the image of a pious authoritarian caliph. However, many of his officials, even those closest to him, were not that religious and frequently crossed the lines drawn by their master. The Ottoman state’s personnel registers (sicill-i aḥvāl defterleri) contain information on disciplinary matters, and one can find many functionaries with drinking problems. Who was drinking when and where? Some had a conservative family and educational background; there were drinkers from ʿulemā and sufi families and with a madrasa education. The article investigates disciplinary measures in modern regulations and whether there were any laws on alcohol consumption by state officials. Against the grain of Istanbul-centred westernisation narratives prioritising educated Ottoman elites, this study will show drinking amongst Muslim officials from the provincial administration with no western language skills and mainly without a high level of education.